HUMOR EXPRESSION IN SARAH SECHAN TALKSHOW - Dewi Purwati (International Journal of Research on English Teaching and Applied Linguistics, 2022)
Humor has a crucial function in talk show because talk show without humor can be flat and boring. Therefore, it is important to investigate types of humor which are occurred in talk show, especially by audience. The focus of this paper is to explore the humor expressions and its function used by host and guest in Sarah Sechan talk show. This study focused on Sarah Sechan talk show in Obrolan Seru Sarah Sechan Bersama Pak Ahok episode which employed the host and guest. To collect data, the researcher downloaded the video from internet with duration one hour and nine minutes. The video of this talk show was obtained, transcribed, and analyzed by using discourse analysis approach. The humor expression used by the host and guest were discussed based on the types of humor of Norrick (1993) and the functions of those humors were analyzed based on Meyer (2000). Findings show that host and guest employed various humors during the talk show. Their humor expression can be as irony, teasing, banter, language play, and joking. In addition, the functions of humors which appear in Sarah Sechan talk show are identification, clarification, enforcement, and differentiation. Findings of this study are relevant in the development of Sarah Sechan talk show particularly to be more creative and interesting talk show for audience.